Oh my gods! : a look-it-up guide to the gods of mythology - Bryant, Megan E. (New York, NY : Scholastic : Franklin Watts, 2010)
Presents a guide to Greek mythology, providing profiles of gods and goddesses along with information on monsters, heroes, and the underworld.
Includes bibliographical references (p. 120-121) and index.
G8
Keywords: Gods, Greek -- Encyclopedias, Juvenile; Mythology, Greek -- Encyclopedias, Juvenile; Gods, Greek -- Encyclopedias; Mythology, Greek -- Encyclopedias